Dark triad personality, resilience, and meaning of life in adolescents who have engaged in self-harm - Qaraan Cotje Noya; Arthur Huwae (Psikostudia : Jurnal Psikologi, 2025)
Adolescents who have committed self-harm often face emotional distress that affects the problem of the meaning of life. This study aims to determine the relationship between dark triad personality and resilience with the meaning of life in adolescents who have committed self-harm. The research method uses a quantitative approach with a multiple correlation analysis design. The sample was early to late adolescents aged 15-21 years who had committed self-harm for one month and had stopped self-harm behavior. The sample involved 434 people and was obtained using incidental sampling. The research instruments consisted of the Short Dark Triad (SD3), the Connor-Davidson Resilience Scale (CD-RISC), and the Meaning in Life Questionnaire (MLQ). The results majorly prove that there is a significant relationship between dark triad personality and resilience in the meaningfulness of life of adolescents who have committed self-harm (F change = 142.881 and sig. = 0.000). The results of the first minor research found that resilience is significantly related to the meaningfulness of life (r = 0.630 and sig. = 0.000). However, the results of the second minor research found the dark triad personality does not show a significant relationship to the meaningfulness of life where Machiavellianism (r = 0.024 and sig.= 0.312), narcissism (r = 0.048 and sig. = 0.173), and psychopathy (r = 0.048 and sig. = 0.158).Remaja yang pernah melakukan self-harm sering menghadapi tekanan emosional sehingga mempengaruhi masalah kebermaknaan hidup. Penelitian ini bertujuan untuk mengetahui hubungan antara dark triad personality dan resiliensi dengan kebermaknaan hidup pada remaja yang pernah melakukan self-harm. Metode penelitian menggunakan pendekatan kuantitatif dengan desain analisis korelasi berganda. Sampel merupakan remaja awal hingga akhir pada usia 15–21 tahun, pernah melakukan self-harm selama satu bulan, dan telah berhenti dari perilaku self-harm. Sampel yang dilibatkan sebanyak 434 orang dan didapatkan dengan menggunakan incidental sampling. Instrumen penelitian terdiri dari Short Dark Triad (SD3), Connor-Davidson Resilience Scale (CD-RISC), dan The Meaning in life (MLQ). Hasil penelitian mayor membuktikan bahwa terdapat hubungan signifikan secara bersama-sama antara dark triad personality dan resiliensi dengan kebermaknaan hidup remaja yang pernah melakukan self-harm (F change = 142,881 dan sig.= 0,000). Kemudian, hasil penelitian minor pertama menemukan bahwa resiliensi berhubungan positif signifikan dengan kebermaknaan hidup (r = 0,630 dan sig.= 0,000). Namun, hasil penelitian minor kedua menemukan bahwa dark triad personality tidak berhubungan signifikan dengan kebermaknaan hidup (machiavellianism dengan nilai F = 0,024 dan sig.= 0,312; narcissism dengan nilai r = 0,048 dan sig.= 0,173; dan psychopathy dengan nilai r = 0,048 dan sig.= 0,158).